PELAKSANAAN PENGHAPUSAN ASET/ BARANG MILIK DAERAH DI SEKRETARIAT DAERAH PROVINSI RIAU TAHUN 2017 - Dwika Wulandari; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study is entitled "The Implementation of the Elimination of Assets / Regional Assets in the Riau Province Regional Secretariat in 2017" This research is motivated by the existence of Regulation of the Minister of Home Affairs No. 19 of 2016 concerning Guidelines for the Management of Regional Assets and Regional Regulations of Riau Province No. 2 of 2013 concerning Management of Regional Property. The formulation of the problem in this study is "Why Has Never Happened the Implementation of the Elimination of Regional Assets / Property in the Riau Province Regional Secretariat in 2017?". The method used in this study is a qualitative method that explains data descriptively. Data collection techniques used were interviews and documentation. While the data source used is primary data obtained from the research location in the form of research informants and subsequently supported by secondary data in the form of documents. The results of this study indicate the condition of Regional Assets / Properties in the Riau Province Regional Secretariat has experienced excess capacity in the storage warehouse. There are 2120 (two thousand and two hundred and twenty) assets / property that are heavily damaged that have not been written off from the Inventory List of Goods belonging to the Riau Province Regional Secretariat so that destruction cannot be carried out and 2 (two) Regional Assets / Properties in the form of Operational Service Vehicles it is proposed to be eliminated through auction and annihilation, and 2 (two) Regional Assets / Assets in the form of buildings and buildings located in the governor's residence complex with Severely Damaged conditions and it is proposed to be eliminated through auction and annihilation. There are obstacles in the Implementation of the Elimination of Assets / Regional Property in the Regional Secretariat of Riau Province in 2017 in the form of the length of the stages of the process of eliminating Regional Assets / Property and the non-maximum evaluation and sale of Regional Assets / Property in the Badan Pengelola Keuangan dan Aset Daerah (BPKAD) of the Province Riau which results in theft and depreciation of the value of Regional Assets / Properties.  Keywords: Implementation, Write Off, Regional Assets / Regional Property